Escepticismo, irreverencia y reformismo. Las imágenes del parlamento argentino en la caricatura y el ensayismo (1880-1912) - Castro, Martín O. (Anuario de Historia de América Latina, 2019)
In Latin America, as in Europe, parliamentary activity was accompanied by satirical criticisms of the poor performance of inefficient assemblies or the privileged nature of the legislature. This negative view of legislative activity did not share homogeneous criteria that would bring together sarcastic editorials, caricatures or portraits of parliamentarians. Particularly from the 1890s to the outbreak of the Great War, criticism of parliament as was shown in irreverent editorials expressed both a regenerationist tone as well as a broader rejection of the parliamentary regime. In Argentina, with the federalisation of the city of Buenos Aires and the establishment of a new Congress after the defeat of porteño forces, an intense debate took shape about the place of the parliamentary institution in the imagination of the conservative republic that was to be built, in part as a result of the relevance of the legislative debates in the 1880s. This article seeks to analyse the criticisms and the images of parliamentary activity, with a focus on the publication of caricatures and essays about the Argentine Congress between 1880 and 1912. It studies the participation of writers and artists who created numerous chronicles and caricatures that displayed sarcasm or criticism of the legitimacy of the parliamentarians, their performance and the impact of personalism on the Argentine political regime. This work also analyses some examples of the satirical press (El Mosquito, Don Quijote, and Caras y Caretas), exploring both their illustrations related to parliamentary activity and their questioning approaches to the contribution of Argentine legislators to the reformist policies at the beginning of the twentieth century.
Keywords: Parliament, Satire, Electoral Reformism, Newspapers